Factorization of a convolution-type integro-differential equation on the positive half line - Khachatryan, A.Kh.; Khachatryan, Kh.A. (Український математичний журнал, 2008)
Sufficient conditions for the existence of a solution of one class of convolution-type integro-differential
equations on half line are obtained. The investigation is based on three factor decomposition of initial
integro-differential operator. Отримано достатні умови для існування розв'язку одного класу інтегро-диференціальних рівнянь типу згортки на півосі. Дослідження базуються на розкладі початкового інтегро-дифе-ренціального оператора на три множники.